On the Frequency of Ocurrence of Cognate Object Constructions in Present-Day British English. A Preliminary Corpus-Based Analysis. - Beatriz Rodríguez Arrizabalaga (Miscelánea: A Journal of English and American Studies, 2016)
Despite having always being a central subject-matter in linguistics due to their controversial syntactico-semantic and pragmatic status, the pragmatic dimension of English cognate object constructions of the type He died a gruesome death and She smiled an enigmatic smile has almost gone unnoticed in the literature. For this reason, and with the intention of shedding some light on the real frequency of occurrence of cognate object constructions in present-day British English, the present paper reports on a preliminary, but thorough and exhaustive, corpus-based analysis in the British National Corpus of the four verbal classes that, according to Levin (1993), seem to be potentially compatible with cognate objects: namely, (i) verbs of nonverbal expression; (ii)manner of speaking verbs; (iii) waltz verbs; (iv) and a fourth class which, including the semantically diverse verbs dream, fight, live, sing, sleep and think, describe recurrent processes and activities in the behaviour of human beings. I will prove, first, that cognate object constructions are not as recurrent in contemporary British English as could be expected a priori and, second, I will account for the main reasons underlying their scarce production.